Patients and relatives as auditors of safe practices in oncology and hematology day hospitals - Isabel Rodrigo Rincón; Isabel Irigoyen Aristorena; Belén Tirapu León; Nicolás Zaballos Barcala; Maite Sarobe Carricas; Joaquín Lobo Palanco; María Luisa Antelo Caamaño; Marta Patricia Martin Vizcaíno; Susan Burnett (BMC, 2021)
Abstract Background When there is a gap in professionals' adherence to safe practices during cancer treatment, the consequences can be serious. Identifying these gaps in order to enable improvements in patient safety can be a challenge. This study aimed to assess if cancer patients and their relatives can be given the skills to audit reliably four safe practices, and to explore whether they are willing to play this new role. Methods We recruited 136 participants in 2018, from the oncology and haematology day hospital of a tertiary hospital in Spain. Patient identification, hand hygiene, blood or chemotherapy identification, and side effects related to transfusion and chemotherapy, were the safe practices selected for evaluation. The study comprised two parts: an interventional educational program and a cross-sectional design to collect data and assess to what degree participants are able and willing to be auditors depending on their characteristics using multivariate logistic regression models. A participant's auditing skill were assessed pre and post the educational intervention. Results The model was seeking predictors of being a good auditor. 63 participants (46.3%) were classified as good auditors after the training. To have younger age, higher educational level and to have had an experience of an adverse event were associated with a higher probability of being a good auditor. Additionally, 106 (77.9%) participants said that they would like to audit anonymously the professionals' compliance of at least three of four safe practices. The willingness to audit safe practices differed depending on the safe practice but these differences did not reach statistical significance. Conclusions The data gathered by patients and relatives acting as auditors can provide healthcare organizations with valuable information about safety and quality of care that is not accessible otherwise. This new role provides an innovative way to engage patients and their families' in healthcare safety where other methods have not had success. The paper sets out the methods that healthcare organizations need to undertake to enrol and train patients and relatives in an auditor role.